Intraindividual variability and micro-structural white matter changes in Alzheimer’s disease - Engelbrecht, Kara (Department of Psychology, 2020)
The costs associated with diagnosis, treatment and care of Alzheimer’s disease (AD) patients places a significant financial and social strain on healthcare systems, patients and caregivers, especially in low-and middle-income countries (LAMICs). Traditional methods for diagnosing AD are time consuming and expensive, and treatments are often only effective in the early stages. These factors call for the development of alternative diagnostic methods. One such method that has gained attention due to its neural overlaps with AD is the measurement of intraindividual variability (IIV; the within-person variation in performance over multiple trials of a single task). IIV researchers have highlighted the role of white matter in increased IIV, and micro-structural white matter changes have been implicated in the early stages of AD. The current study examined the relationship between IIV on simple and choice reaction time tasks and micro-structural white matter changes, as indexed by fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (DA) and radial diffusivity (DR) in a sample of 16 AD patients and 20 healthy older adults. Across the entire sample, increased IIV on both the simple and choice reaction time tasks was significantly correlated with lower FA in an area of the right hemisphere inferior longitudinal fasciculus (R-ILF). Increased IIV on the choice reaction time task was significantly correlated with lower DA in the same area. Finally, IIV on the choice reaction time task contributed significantly and uniquely to variance in DA in the same area. These results suggest that further longitudinal studies into the diagnostic utility of IIV for neurological disorders might be of value for clinicians, patients and caregivers.